Factors Affecting Healthcare Professional’s Adoption Of The Electronic Medical Records Systems - Bouhadjeb ,Madjida; Terbeche ,Mohamed (جامعة الوادي University of Eloued, 2024)
The purpose of this research is to examine the factors affecting the use of Electronic Medical Records (EMR) by medical staff members, including doctors and nurses, at Shabaan Hamdoun Hospital in Maghnia, Tlemcen Province. In order to investigate their effects on healthcare professionals' desire to embrace the system and its actual use, the study used the Technology Acceptance Model (TAM) and added external variables such data security, self-efficacy, management support, and infrastructure. A custom created questionnaire was used to gather information from a sample of 156 healthcare professionals, drawn from a population of 381 healthcare workers. Using SPSS 27, multiple linear regressions were used to evaluate the data and look at the correlations between the variables. The findings demonstrated that healthcare professionals' intention to use electronic medical records is positively and directly influenced by perceived usefulness, ease of use, data security, self-efficacy, and management support. While infrastructure had no significant impact, suggesting it may not be the primary barrier. Additionally, the actual use of the system was strongly and positively affected by the intention to use.
Keywords: Electronic Medical Records; Health System; Healthcare Professionals; Technology Acceptance Model.